1988
DOI: 10.2113/gsecongeo.83.7.1401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative elemental and oxygen isotope geochemistry of jasperoid in the northern Great Basin; evidence for distinctive fluid evolution in gold-producing hydrothermal systems

Abstract: This comparative geochemical study of jasperoid in the northern Great Basin is based on 65 samples from 10 Carlin-type gold deposits and 22 similar but apparently barren hydrothermal systems. Multielement geochemistry coupled with oxygen isotope data indicate that hydrothermal fluids in barren and mineralized systems evolved in different ways, and that there are fundamental geochemical differences among the various gold-producing deposits of the area.Much of the variation in the jasperoid geochemical data can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A regional study of the oxygen isotope compositions ofjasperoids in the eastern Great Basin (Holland et al, 1988) reports that jasperoids associated with Au deposits generally have 61sO values of 8 to 20 per rail, whereas barren jasperoids have lighter oxygen. All the values reported here fall within the productive range regardless of their proximity to ore or stratigraphic position, but Joana and Chainman jasperolds do not in general host even subore-grade mineralization.…”
Section: Chemical Evolution Of Alteration: the Geological And Geochemmentioning
confidence: 99%
“…A regional study of the oxygen isotope compositions ofjasperoids in the eastern Great Basin (Holland et al, 1988) reports that jasperoids associated with Au deposits generally have 61sO values of 8 to 20 per rail, whereas barren jasperoids have lighter oxygen. All the values reported here fall within the productive range regardless of their proximity to ore or stratigraphic position, but Joana and Chainman jasperolds do not in general host even subore-grade mineralization.…”
Section: Chemical Evolution Of Alteration: the Geological And Geochemmentioning
confidence: 99%
“…Because jasperoid is commonly the most prominent outcropping rock in sediment-hosted micron gold deposits and because it is also found in other types of hydrothermal systems, considerable attention has been given to the possibility of discriminating between jasperoids from barren and mineralized micron gold systems. Most of these studies have concentrated on trace-element and isotopic characteristics (Holland et al, 1988;Nelson, 1990 ). Haynes and Kesler ( 1988 ) noted that fluid inclusion gas geochemistry could have some advantages in evaluation of jasperoids because the inclusion gases should be more homogeneously distributed than gold and other metals.…”
Section: Introductionmentioning
confidence: 99%
“…Theodore and Jones (1992) stated that gold concentrations in jasperoids are typically very spotty because sedimentary-hosted Au-Ag deposits along the Carlin trend of north-central Nevada contain jasperoids commonly showing insignificant gold concentrations in one sample and anomalously high concentrations in another sample only several meters away. Recent studies of jasperoids from the northern Great Basin also confirmed an extreme variability in elemental concentrations in suites of samples obtained from a single deposit (Holland et al, 1988). In addition, many of the sedimentary-hosted Au-Ag deposits along the Carlin trend and the Preble-Pinso-Getchell alignment show a zonation from distal carbonate veins, through mixed carbonatejasperoid veins, to jasperoid-only mineralized veins proximal to the deposits (Madrid and Bagby, 1988).…”
Section: Introductionmentioning
confidence: 83%